PENGARUH GAYA HIDUP, KONSEP DIRI, KELAS SOSIAL DAN HARGA TERHADAP KEPUTUSAN KONSUMEN BERKUNJUNG KE KEDAI KOPI (Studi Kasus Pada Kedai Kopi XYZ di Samarinda) - Silvana Kardinar Wijayati; Widya Hana Fahleti; Johan Arianto (LPPM University 17 Agustus 1945 Samarinda, 2019)
Coffee has been becoming a popular commodity in Indonesia. The shift of people’s lifestyles and preferences have been creating new trend in business. Coffee shops are now almost everywhere in urban areas. Marketers need to study variables affecting customer purchase/visit decision to coffee shop so they can come up with maketing programs suit to target market. The purpose of this study is to determine the effect of lifestyle, self concept, social class and price simultanously and partially on customer visit decision to coffee shop. Data collected with self-administered questionnaire distributed to 73 customers of a coffee shop in Samarinda City. Sample was collected using accidental sampling technique. Multiple linear regression in SPSS Version 22 used to analyze the data and it is revealed that social class and self concept positively and significantly affect customer purchase/visit decision. On the other hand, price found negatively and significantly affect customer purchase/visit decision to coffee shop XYZ. Whie lifestyle negatively but insignificanty affects purchase/visit decision. The results of this study suggest marketeres to use different marketing programs to different target markets.